Hubungan Inisiasi Menyusu dini, dukungan keluarga dan motivasi ibu dengan keberhasilan pemberian ASI esklusif di Wilayah Kerja Puskesmas Burnai Mulya tahun 2024 - Suryanti, Kadek; Afrika, Eka; Dharmayanti, Reffi; Dewi, Ratna (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
Providing proper nutrition in the first six months of a baby's life is by providing exclusively breast milk. Optimal breastfeeding can save the lives of more than 820,000 children under 5 years old every year. The coverage of babies receiving exclusive breastfeeding in 2020 was 66.06% and there was a decrease in 2021, namely 56.9%. The coverage of exclusive breastfeeding collected in South Sumatra Province in 2020 was 51.6%, a decrease compared to 2019 (57.8%) and has not yet reached the program target. The aim of this research is to determine the relationship between early initiation of breastfeeding, family support and maternal motivation simultaneously with the success of providing exclusive breastfeeding in the Burnai Mulya Community Health Center Work Area in 2024. Type and Design of this research is quantitative using an analytical survey method with a cross sectional approach. The population in this study was all mothers who had babies aged 7-12 months at the Burnai Mulya Community Health Center in 2024, totaling 304 people. The sample used was 75 respondents. The sampling technique in this study used an accidental sampling technique. The results of univariate analysis obtained from 75 respondents, there were 48 respondents (64.0%) who provided exclusive breastfeeding and 27 respondents (36.0%) who did not. The results of the chi-square statistical test on the early breastfeeding initiation variable obtained ρ value = 0.022, the family support variable ρ value = 0.019 and the motivation variable obtained ρ value = 0.006 which is smaller than α=0.05 indicating there is a relationship between early breastfeeding initiation and family support and motivation. by providing exclusive breastfeeding in the Burnai Mulya Community Health Center working area in 2024. It is hoped that suggestions for the Burnai Mulya Community Health Center can be used as a source of information for the community health center in an effort to increase the coverage of exclusive breastfeeding and to find out what factors can influence mothers in providing exclusive breastfeeding.